Leituras sobre representações imagéticas femininas negras em livros didáticos de história (1997-2014) - Carvalho, Rayssa Andrade (2015)
This present dissertative paper proposes us a reading through visual images that portray black women In the textbooks of History for elementary school produced in 1997 and 2010 and currently in use at public schools from João Pessoa-PB, from 2000 to 2001 and between 2013 and 2014. This study ties in with the History of Education, linked to the following research area Teaching of History and Historical Knowledge, focused on Historical Culture. Thus, this study was grounded by studies of Choppin (2004); Bittencourt (2004) Gatti Jr. (2004) Cassiano (2007) Munakata (2012), dealing with processes of production, choice and textbooks distribution. For this research, we used quantitative and qualitative methodologies, hence, we mapped the History textbooks distributed during the period of time aforementioned, then we came to the following titles: História – Edição Reformulada, with 1997 edition, of the Editora FTD e Projeto Araribá História, with 2010 edition, of the Editora Moderna. Futhermore, based on the theoretical perspective of Chartier (2002), we considered the black female representations made in the literary texts of XIX century, in the novel Casa Grande e Senzala de Freyre (2003) and in the textbook produced from 1980 to 2010. To analyse the iconographies present in the school-books we used studies by Mauad (2007) and Bueno (2011), setting up a method of images reading. This way, we observed the black female images stereotyped in the contents from the History of Brazil, seeking to discuss changes and continuity in the representations enshrined by the school historiography, as in "mulatto" and "black mother", produced by the literary messages, doctors and oficial historiography. Therefore, we comprehend that the representations contained in the visual images of History textbooks may influence on the students' identity construction.